ANALYSIS OF MURABAHAH FINANCING MANAGEMENT IN SHARIA FINANCIAL INSTITUTIONS ACCORDING TO PSAK 102: STUDY OF SHARIA ACCOUNTING PRACTICES - Nursyidah; Syawal Harianto; Haris Al Amin (CV. Radja Publika, 2021)
Islamic banks provide a financial solution for individuals who have surplus funds and wish to channel them towards those who require funding. One way in which banks can distribute funds to the community is through the sale and purchase of goods based on sharia principles, such as murabaha, salam and istishna. At PT Bank Aceh Syariah, murabahah financing is popular among customers, which adheres to the sharia principles as per the DSN-MUI Fatwa No. 4/DSN-MUI/IV/2000, while the accounting standards used are PSAK No. 102 and PAPSI 2013 for Islamic Banking Accounting Guidelines. The aim of this study is to examine the application of sharia accounting practices at PT Bank Aceh Syariah by analyzing the suitability of murabahah financing in accordance with the guidelines set out in the DSN-MUI Fatwa, PSAK No. 102, and PAPSI 2013. This research uses a qualitative approach to analyze the implementation of murabahah accounting at PT Bank Aceh Syariah, using both fieldwork and library research.The study findings reveal that the implementation of murabahah financing at PT Bank Aceh Syariah is in compliance with sharia principles, as per the DSN-MUI Fatwa, and accounting standards, as per PSAK No. 102 and PAPSI 2013, in terms of recognition, measurement, presentation, and disclosure. However, PT Bank Aceh Syariah does not impose any penalty on customers who experience delays or arrears in repayment. This policy is based on a decision by the Sharia Supervisory Board (DPS) of PT Bank Aceh Syariah, which states that penalties are not allowed in the bank's operations.